Cost-effectiveness analysis of a cluster-randomized, culturally tailored, community health worker home-visiting diabetes intervention versus standard care in American Samoa - Shuo J. Huang; Omar Galárraga; Kelley A. Smith; Saipale Fuimaono; Stephen T. McGarvey (BMC, 2019)
Abstract Background Type 2 diabetes mellitus (T2DM) is highly prevalent in American Samoa. Community health worker (CHW) interventions may improve T2DM care and be cost-effective. Current cost-effectiveness analyses (CEA) of CHW interventions have either overlooked important cost considerations or not been based on randomized clinical trials (RCTs). The Diabetes Care in American Samoa (DCAS) intervention which occurred in 2009-2010 was a cluster-randomized, culturally tailored, home-visiting CHW intervention and improved HbA1c levels. Objective To analyze the cost-effectiveness of the DCAS intervention against standard care using a RCT in a low-resource setting. Methods We collected clinical, utilization, and cost data over 2 years and modeled quality-adjusted life years (QALYs) gained based on the RCT glycated hemoglobin (HbA1c) improvements. We calculated an incremental cost-effectiveness ratio (ICER) from the societal perspective over a 2-year time horizon and reported all costs in 2012 USD ($). Results Two hundred sixty-eight American Samoans diagnosed with T2DM were cluster randomized into the CHW (n = 104) or standard care control (n = 164) arms. The CHW arm had a mean reduction of 0.53% in HbA1c, an increase of $594 in cost, and an increase of 0.05 QALYs. The ICER for the CHW arm compared to the control arm was $1121 per percentage point HbA1c reduced and $13 191 per QALY gained. Conclusions Compared to a variety of willingness-to-pay thresholds from $39 000 to $154 353 per QALY gained, this ICER shows that the CHW intervention is highly cost-effective. Future studies of the cost-effectiveness of CHW T2DM interventions in similar settings should model lifetime costs and QALYs gained to better assess long-term cost-effectiveness. Trial registration ClinicalTrials.gov, ID NCT00850824. Registered 9 February 2009, https://clinicaltrials.gov/ct2/show/NCT00850824.